La fotografia nel museo d’arte a fine Ottocento: sovrapposizioni e occasioni per una rinnovata filologia visiva. Alcuni spunti - Levi, Donata (Rivista di studi di fotografia. Journal of Studies in Photography, 2020)
The article deals with the effects of photography on the practices of art historians, focusing on some German cases. Photography, defined by Paul de Saint-Victor in 1887 as the “musée en action de l’art européen,” offered unprecedented opportunities for a renewed visual philology. Yet this evolution was more complex and less unidirectional than is generally thought. The illustrated publications of Gustav Scheuer in the 1860s attest to different ways of manipulating photographic images and illuminate the connections between photography and comparative methods, which initially concerned the relationships between original paintings and photographs much more than those among paintings themselves.